Utilizing Maternal Height as a Predictor for Childhood Stunting Prevention: A Health Promotion Strategy Rooted in Early Risk Identification - Nur Alam Fajar; Iche Liberty; Esti Sri Ananingsih; Risa Nur Amalia (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: In this study, we aimed to examine the potential of maternal height assessment as a cornerstone of stunting prevention strategies within health promotion frameworks. Methods: This case-control study was conducted from April to December 2024 across 15 stunting locus villages in Banyuasin Regency, South Sumatera, Indonesia. Toddlers aged 6–59 months were selected through stratified random sampling, with stunting defined as height-for-age Z-score < -2 SD based on WHO 2006 standards. Cases and controls were matched by age, sex, and residence. Data were collected through interviews with mothers and anthropometric measurements. Children with chronic illness or incomplete records were excluded. Data analysis used STATA 15.0 with p < 0.05. Ethical approval was granted by Universitas Sriwijaya, and written informed consent was obtained from all participants. Results: Maternal height was significantly associated with stunting (p < 0.001), with shorter average height in mothers of stunted children. Discriminant analysis supported this finding (canonical correlation = 0.254, p < 0.001). Although not statistically significant, a trend toward stunting was observed, which may reflect underlying epidemiological patterns consistent with the multifactorial nature of growth faltering in early childhood. Such exploratory findings highlight potential pathways that warrant further investigation within a life-course and social determinants of health framework. Environmental factors such as water access and sanitation showed no significant associations. Conclusion: In conclusion, maternal height is a significant and practical discriminant of childhood stunting. Integrating height screening into maternal care may enhance early risk identification. Future research should validate these findings across populations and explore additional biological, environmental, and behavioral factors influencing stunting outcomes.